DETERMINANTS OF HIGH-TECH EXPORTS OF ASEAN5+3 COUNTRIES - Priyahasini, Sevanesan (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aims to study the determinants of high-tech product exports in ASEAN5+3 countries. The study carries out from 2000-2019 which comprises of eight countries which is Malaysia, Thailand, Indonesia, Philippines, Singapore, Japan, South Korea, and China. This study will provide better understanding about what high-tech exports is and what are the determinants of high-tech exports. There are four variables used to indicate the determinants of high-tech exports of ASEAN 5+3 countries. The methodologies applied in this study are panel unit root test and diagnostics tests which include panel cointegration test, Granger Causality test and among the few. The empirical results from panel cointegration, DOLS and FMOLS estimators illustrate that there is evidence of long-run relationship among the high-tech export of the selected countries. Granger causality test was implemented to verify the causality relationship among the variables. The data employed in this study does not have unit root and the results shows that foreign direct investment and institutional quality are significant whereas patent applications resident and gross capital formation are insignificant. Thus, some recommendations had been developed for each country to enhance the export of high-tech products.